СТРУКТУРА СУБ’ЄКТНО-ТВОРЧОЇ АКТИВНОСТІ СТУДЕНТІВ ІНСТИТУТІВ МИСТЕЦТВ ПЕДАГОГІЧНИХ УНІВЕРСИТЕТІВ - Лібінь, Цзян (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Стаття розкриває специфіку структурної побудови суб’єктно-творчої активності майбутніх учителів музики. Суб’єктно-творча активність розглянута як ключовий елемент педагогічного процесу, який вимагає перегляду, переоцінки всіх компонентів фахової підготовки майбутнього вчителя музики. Це радикально змінює саму сутність і характер підготовки вчителя, ставлячи в центр уваги саме студента, виокремлюючи з цього процесу розвиток його особистості. Відповідно теоретико-методологічним основам означеного процесу, нами розроблена структура суб’єктно-творчої активності майбутніх учителів музики, що вбирає мотиваційно-потребовий, емоційно-когнітивний та творчо-діяльнісний компоненти. Суб’єктно-творча активність реалізується шляхом послідовної індивідуалізації всього педагогічного процесу, врахування індивідуально-типологічних особливостей студента, його персоналізації. Статья раскрывает специфику структурного построения субъектно-творческой активности будущих учителей музыки. Субъектно-творческая активность рассмотрена как ключевой элемент педагогического процесса, который требует пересмотра, переоценки всех компонентов профессиональной подготовки будущего учителя музыки. Это радикально меняет саму сущность и характер подготовки учителя, поставив в центр внимания именно студента, выделяя из этого процесса развитие его личности. Согласно теоретико-методологическим основам указанного процесса нами разработана структура субъектно-творческой активности будущих учителей музыки, которая включает мотивационно-потребностный, эмоционально-когнитивный и творчески-деятельный компоненты. Субъектно-творческая активность реализуется путем последовательной индивидуализации всего педагогического процесса, учета индивидуально-типологических особенностей студента, его персонализации. The article reveals the specific subject-structural construction creative activity of the future teachers of music. Subject-creative activity is considered a key element of the pedagogical process that requires revision, revaluation of all components of the professional training of future teachers of music. This radically changes the very essence and nature of teacher training, putting in focus is a student, isolating this process of development of his personality. Accordingly, theoretical and methodological foundations definite process we developed a structure subject-creative activity of the future teachers of music that absorbs potrebovyy motivational, emotional, cognitive and creative-activity components. Potrebovyy motivational component (criterion – the presence of motivational orientation to professional growth and the need for specialized skills acquired in the process of conducting and choral studies) presented by the following indicators: the presence of cognitive interest to professional activities; expression of interest in conducting and choral studies; availability of professional orientation for performing and teaching activities. Emotional and cognitive component (criterion – a measure of formation of emotional and cognitive state of creative activity and initiative) represented by the following indicators: the desire of acquiring professional knowledge and skills; empatiynoho expression of empathy in dealing with choral works; train to explore the best examples of Choral Singing. Action-projective component (criterion - a measure of independence in the approach to the interpretation of artistic and musical images of choral works in performing activities) represented factors: the need for selection of methods for solving creative problems; capacity for understanding and developing subject-creative activity in professional activities; capacity for critical evaluation of their own performance. Subject-creative activity is realized through individualization coherent whole educational process, taking into account individual student typological characteristics, its personalization.